Brain Computer Interface Based Prosthesis Control - Rana, Hania Fayyaz (2005)
A Master of Science Thesis in Mechatronics Engineering Submitted by Hania Fayyaz Rana, "Brain Computer Interface Based Prosthesis Control," July 2005. Supervised by Dr. Hassan Al-Nashash and Dr. Yousef Al-Assaf. Thesis available only in hard copy in Reference and AUS Archives